2020
DOI: 10.1007/s00425-020-03388-0
|View full text |Cite
|
Sign up to set email alerts
|

The developmental and iron nutritional pattern of PIC1 and NiCo does not support their interdependent and exclusive collaboration in chloroplast iron transport in Brassica napus

Abstract: Main conclusion The accumulation of NiCo following the termination of the accumulation of iron in chloroplast suggests that NiCo is not solely involved in iron uptake processes of chloroplasts.Abstract Chloroplast iron (Fe) uptake is thought to be operated by a complex containing permease in chloroplast 1 (PIC1) and nickel-cobalt transporter (NiCo) proteins, whereas the role of other Fe homeostasis-related transporters such as multiple antibiotic resistance protein 1 (MAR1) is less characterized. Although piec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 94 publications
0
31
0
Order By: Relevance
“…3a,b), which strongly suggests that ARG1 on the chloroplast membranes probably transports Co and Ni from the chloroplast to the cytoplasm. A chloroplast envelope protein NiCo, as a member of the Ni/Co transporter family, increasingly accumulates following leaf development and has been suggested to be involved in Co and Ni uptake into chloroplasts (Duy et al ., 2011; Pham et al ., 2020). Hence, NiCo and ARG1 may be responsible for the transport of Co and Ni into and out of chloroplasts, respectively, so as to maintain together Co and Ni homeostasis in chloroplasts.…”
Section: Discussionmentioning
confidence: 99%
“…3a,b), which strongly suggests that ARG1 on the chloroplast membranes probably transports Co and Ni from the chloroplast to the cytoplasm. A chloroplast envelope protein NiCo, as a member of the Ni/Co transporter family, increasingly accumulates following leaf development and has been suggested to be involved in Co and Ni uptake into chloroplasts (Duy et al ., 2011; Pham et al ., 2020). Hence, NiCo and ARG1 may be responsible for the transport of Co and Ni into and out of chloroplasts, respectively, so as to maintain together Co and Ni homeostasis in chloroplasts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results support the role of FPN3/IREG3 as an iron exporter of mitochondria and chloroplasts, based on the yeast data (Figure 2) and iron accumulation quantified by ICP-MS with isolated chloroplasts and mitochondria (Figure 7G, H). It is noteworthy that in a recent study, BnMAR1, the FPN3/IREG3 ortholog in Brassica napus , was speculated to be involved in iron release from the plastids based on the correlation between its gene expression and chloroplast iron content (Pham et al , 2020). Although the mechanism of transport via FPN has not been fully understood, structural and biochemical studies indicated that the bacterial FPN3 ortholog, BdFPN, transports iron and other divalent cations along their concentration gradient in a uniporter-like manner (Taniguchi et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The ferric chelate reductase, FRO7, reduces iron for chloroplast iron acquisition (Jeong et al , 2008), and PERMEASE IN CHLOROPLAST 1 (PIC1) mediates iron transport into chloroplasts via interaction with NiCo (Duy et al , 2007; Duy et al , 2011). A recent study in Brassica napus proposes that NiCo may also be involved in iron sensing or iron release from chloroplasts (Pham et al , 2020). The Arabidopsis MitoFerrinLike1 (Mfl1) has also been reported to import iron into chloroplasts (Tarantino et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ABCI11/NAP14 was shown to play a crucial role in Fe homeostasis ( Voith von Voithenberg et al, 2019 ). Furthermore, recently, NiCo was indicated not participating in the uptake together with PIC1 in an exclusive manner ( Pham et al, 2020 ). Chloroplast NEET protein exports Fe–S clusters to cytoplasmic Fe–S proteins.…”
Section: Introductionmentioning
confidence: 99%
“…RNAi of At-NEET resulted in developmental retardation, increased senescence and elevated sensitivity to low and decreased sensitivity to high Fe nutrition ( Nechushtai et al, 2012 ; Lu, 2018 ). Indeed, little is known on the Fe release from chloroplasts to date ( Vigani et al, 2019 ; Pham et al, 2020 ). Although Fe is an essential micronutrient for all living things, free ferrous Fe ions can catalyse Fenton reactions ( Halliwell and Gutteridge, 1992 ); thus, accumulation of Fe in supraoptimal concentration can lead to the production of ROS ( Ravet et al, 2009 ; Briat et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%